FACTORS INFLUENCING INTENTION TO USE E-LEARNING BY AGRICULTURAL EXTENSION AGENTS IN MALAYSIA (Journal of Technology and Operations Management, 2017)
The application of e-learning has extended beyond the traditional educational establishments to various other areas including agricultural sector. In agricultural sector, extension services are perhaps the key beneficiary of e-learning, being in the unique position as an intermediary between agricultural specialists and farmers. Hence the objective of this study was to investigate the relationship between attitude, subjective norm, perceived behavioral control, management support and training; and the intention to use e-learning technology among agricultural extension agents in Malaysian agricultural sector. This quantitative study was based on Theory of Planned Behavior with management support and training as additional constructs. While there were many studies that investigated factors affecting intention to use e-learning in educational institutions, there were limited studies of the same in the context of extension agents in agriculture setting. The results showed that all of the hypotheses developed by the previous authors were supported by the study, and further revealed that management support is the most important determinant of agricultural extension agent’s intention to use e-learning, followed by attitude. Finally, the implications of this study were discussed, and further research directions were proposed.